A simple method for DNA extraction from activated sludge - Dounghatai Singka (2018)
© 2012, Chiang Mai University. All rights reserved. A protocol for DNA extraction directly from activated sludge is described. Sludge samples were lysed by glass bead and CTAB. The extracted DNA was purified with phenol: chloroform: isoamyl alcohol mixture and precipitated in sodium acetate and isopropanol. The proposed protocol is simple, rapid and required small sample size, yielding about 40.5 ± 1.8 μg DNA g-1sludge. The quality of DNA is good enough for successful PCR amplifications of 16S rDNA, 16S rDNA V3 region and denaturing gradient gel electrophoresis (DGGE) analysis of archaeal population. This described method can also be applied to other environmental samples such as whey and soil.